Nótula crítica sobre a hodierna involução dos direitos fundamentais e dos direitos humanos - Rodrigues, Luís Manuel Barbosa,1962- (2020)
Lusíada. Direito. - ISSN 2182-4118. - S. 2, n. 23-24 (2020). - p. 187-194.